Risk Factors of Pneumonia in Children under Five in Lewoleba Hospital, East Nusa Tenggara, Indonesia - Nikosius Dae Sory Wutun; M Dinah Charlota Lerik; Muntasir Muntasir (Masters Program in Public Health, 2020)
Background: Pneumonia is an infection of the res